2019
DOI: 10.3389/fpls.2019.00237
|View full text |Cite
|
Sign up to set email alerts
|

Root Branching and Nutrient Efficiency: Status and Way Forward in Root and Tuber Crops

Abstract: Plants are immobile organisms that require roots to efficiently and cost-effectively exploit their habitat for water and nutrients. Plant root systems are dynamic structures capable of altering root branching, root angle, and root growth rates determining overall architecture. This plasticity involves belowground plant-root mediated synergies coupled through a continuum of environmental interactions and endogenous developmental processes facilitating plants to adapt to favorable or adverse soil conditions. Pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 101 publications
0
34
0
Order By: Relevance
“…Similarly, higher numbers of root stage‐specific genes were found at 30 DAT, which is a major morphological event in storage root formation and bulking (Wang et al ., ). Moreover, P and K also play important roles during storage root formation at the early stage (30–40 DAT) (Wang et al ., ; Duque & Villordon, ). Results of this and previous research suggests that the early growth stage (30–40 DAT) is an important time period for efficient nutrient (N, P, K) use, which regulates storage root formation in sweet potato.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similarly, higher numbers of root stage‐specific genes were found at 30 DAT, which is a major morphological event in storage root formation and bulking (Wang et al ., ). Moreover, P and K also play important roles during storage root formation at the early stage (30–40 DAT) (Wang et al ., ; Duque & Villordon, ). Results of this and previous research suggests that the early growth stage (30–40 DAT) is an important time period for efficient nutrient (N, P, K) use, which regulates storage root formation in sweet potato.…”
Section: Discussionmentioning
confidence: 99%
“…Research also found that 30–40 DAT (days after transplanting) was an important stage for storage root formation and bulking, even under nutrient stress. Low P can modify root cortical aerenchyma‐like structure formation at 30 DAT (Duque & Villordon, ), while sufficient K (potassium) is beneficial for storage root formation and yield at 40 DAT (Wang et al ., ). Moreover, 30 DAT is a major morphological event when higher numbers of root stage‐specific genes have been observed (Wang et al ., ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over 4100 species of plant-parasitic nematodes are distributed globally and cause huge agricultural losses ($80~173 billion) annually [ 1 3 ]. Among them, Ditylenchus destructor Throne, commonly known as potato rot nematode or stem nematode, is one of the primary pathogens in the global production of sweet potato ( Ipomoea batatas ) and potato ( Solanum tuberosum ), the two main root and tuber crops essential for food security [ 4 , 5 ]. In China, the country producing 75% production of world sweet potato, D .…”
Section: Introductionmentioning
confidence: 99%
“…To meet the demands of plant growth and survival, the root system needs to develop a large number of lateral roots to increase root space in the soil [2]. Plants with well-developed lateral root system usually have better nutrient absorption capabilities and higher yields [3].…”
Section: Introductionmentioning
confidence: 99%